A novel relay selection algorithm using ant colony optimization with artificial noise for secrecy enhancement in cooperative networks. (19th July 2018) - Shemi, P.M.; Jibukumar, M.G.; Sabu, M.K.
Summary: Cooperative communication is one of the fastest growing research areas of today. It can efficiently mitigate the effect of shadowing and fading with the help of relays and proper relay selection technique. In this paper, a novel relay selection scheme combined with artificial noise (AN) is devised to enhance the secrecy of cooperative networks with amplify‐and‐forward scheme, over Rayleigh fading channels in the presence of a passive eavesdropper. The probability of path selection of ant colony optimization algorithm is used for selecting the best relay with high end‐to‐end signal‐to‐noise ratio. The probability of choosing a path depends on the significance of channel gain ( G ) and fading coefficients ( h ). The proposed algorithm finds the best relay in the following wireless scenarios: when (i) both channel gain and fading coefficients are significant; (ii) only fading coefficients are significant; and (iii) only channel gain is significant. Because the direct links between source and destination and source and eavesdropper are considered, AN along with the information is sent by both the source and the selected relay. The performance is evaluated based on secrecy rate ( R s ); for the relays randomly placed between the source and destination and for different eavesdropper's location. The results show that the proposed relay selection scheme achieves better secrecy for different wireless scenarios compared with traditional schemes. With the help of AN, the secrecy rate can be made positive even when the eavesdropper lies near to source. Abstract : In this paper, a novel relay selection algorithm based on Ant Colony Optimization for two cooperative schemes, namely, amplify‐and‐forward (AF) and amplify‐and‐forward with artificial noise (AF‐AN) in the presence of a passive eavesdropper is proposed. The practical case where relays are randomly distributed between source and destination; direct links between source‐destination and source‐eavesdropper are considered here for the analysis. Numerical results are presented in terms of secrecy rate with different eavesdropper position, in comparison with conventional direct transmission schemes.